Innovative Chemistry Laboratory Models in 21st Century Learning: A Literature Review on the Development of Scientific Creativity and Science Process Skills - Nada Clairina Sophian; Gesti Maharani; Sura Juddin (Indonesian Publication Center, 2026)
Conventional chemistry laboratory activities based on a cookbook approach have proven insufficient in developing students’ scientific creativity and science process skills (SPS) for the 21st century. This gap is reflected in persistently low scores on originality and elaboration dimensions of creative thinking, as well as weak hypothesis formulation and experimental design skills. Despite the growing body of research on innovative laboratory practices, no comprehensive synthesis has systematically mapped the empirical evidence across multiple innovative models, compared their relative effectiveness, and identified contextual limitations, particularly for developing-country settings such as Indonesia. This research gap motivates the present study. This systematic literature review examines 42 empirical articles selected from an initial pool of over 200 studies through PRISMA screening, and analyzes innovative laboratory models empirically tested over the past decade (2016–2025), including Project-Based Learning (PjBL), Inquiry-Based Learning (IBL), STEM integration, virtual laboratories, ethnoscience-based practicum, and Green Chemistry principles. Findings consistently show that these models enhance all four dimensions of scientific creativity (fluency, flexibility, originality, elaboration) as well as integrated SPS. Quantitatively, PjBL and IBL interventions yielded the strongest effect sizes (d = 0.72–1.14) on creativity and integrated SPS dimensions, with the originality and elaboration dimensions showing the most pronounced gains compared to conventional approaches. PjBL and IBL proved most effective in stimulating divergent thinking, while virtual laboratories reduced cognitive load on abstract content. Despite challenges such as infrastructure limitations and teacher readiness, locally sourced materials and microscale experiment designs offer affordable and practical solutions. Concrete recommendations for educators and policymakers are provided to modernize the design of chemistry practicums sustainably.